RELATIONS BETWEEN THE MEMBER STATES OF THE COOPERATION ORGANIZATION OF TURKIC-SPEAKING COUNTRIES IN THE FIELD OF HEALTH, ALTERNATIVE ENERGY AND AGRICULTURE - Shodiqulov Eldor Sherzodovich (Western European Studies, 2023)
In this article, the member states of the international structure are presented with opportunities for discussion and deepening of cooperation and its development, development of close relations between Turkic-speaking countries, development of mutual trust, friendship, good neighborliness, stability and support of cooperation. They talked about the political issues of development, the provision of common problems in the world and the whole world, and the organization with interests.
Keywords: Energy sector; supply chain; forum